PICTURES AS LEARNING – TEACHING AID IN IMPROVING ENGLISH VOCABULARY AT ELEMENTARY SCHOOL IN DENPASAR - Ni Luh Putu Unix Sumartini (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2023)
It has been researched in some studies and related theories confirming that using picture in teaching English vocabulary was very effective. Especially for young learner in elementary school which has Bahasa Indonesia as their main language, the vocabulary problem used to occurred in spelling, pronunciation, grammatical use, and meaning. Those language aspects become main obstacle for them. This research explores the implementation of English vocabulary and to find out the score improvement in using picture in learning process. The objective of this research is to find out the effectiveness of picture in improving students’ vocabulary. The research is conducted in Santo Yoseph 1 elementary school Denpasar in the class of 3B .It was conducted in two cycles to twenty-seven participants. Instruments used were tests, questionnaires, and observation. Results showed that an initial vocabulary mastery was 75.6 points, and increased to 86.08 in the final cycle of the study. In the same way, the questionnaire results in the second cycle revealed that although the students still found English learning (85.50) and memorizing vocabulary (70.37%) difficult, their interest in learning it increased (59.26% from 29.63%). Finally, the observation results of the second cycle also showed the improvement of both students’ and teacher’s teaching and learning atmosphere as well as interest. However, a further study and learning policy are worthy to assure the application of the pictorial aids facilitating the attractive and motivating learning atmosphere in the future. Keywords: Secondary student, vocabulary, pictorial aid